In vivo evaluation of an innovative synbiotics on stage IIIb-IV chronic kidney disease patients - Vacca, Mirco; Celano, Giuseppe; Calabrese, Francesco Maria; Rocchetti, Maria Teresa; Iacobellis, Ilaria; Serale, Nadia; Calasso, Maria; Gesualdo, Loreto; De Angelis, Maria (Frontiers in Nutrition, 2023)
Microbiota unbalance has been proven to affect chronic kidney disease (CKD) patients and, noteworthy, microbiota composition and activity are implicated in CKD worsening. The progression of kidney failure implies an exceeding accumulation of waste compounds deriving from the nitrogenous metabolism in the intestinal milieu. Therefore, in the presence of an altered intestinal permeability, gut-derived uremic toxins, i.e., indoxyl sulfate (IS) and p-cresyl sulfate (PCS), can accumulate in the blood. In a scenario facing the nutritional management as adjuvant therapy, the present study assessed the effectiveness of an innovative synbiotics for its ability to modulate the patient gut microbiota and metabolome by setting a randomized, single-blind, placebo-controlled, pilot trial accounting for IIIb-IV stage CKD patients and healthy controls. Metataxonomic fecal microbiota and fecal volatilome were analyzed at the run-in, after two months of treatment, and after one month of wash out. Significant changes in microbiota profile, as well as an increase of the saccharolytic metabolism, in feces were found for those CKD patients that were allocated in the synbiotics arm. Noteworthy, the here analyzed data emphasized a selective efficacy of the present synbiotics on a stage IIIb-IV CKD patients. Nonetheless, a further validation of this trial accounting for an increased patient number should be considered.